Impacts of copper contamination on a rocky intertidal predator-prey interaction. (January 2021) - Pardal, André; Martinez, Aline S.; Christofoletti, Ronaldo A.; Karythis, Simon; Jenkins, Stuart R.
Abstract: Metal contamination can change ecological interactions with potential effects on community dynamics. However, understanding real effects of metals on biota relies on studies undertaken in natural conditions. Through a field experiment, we investigated the effects of copper contamination on the responses of a barnacle prey and its predator, the dogwhelk, and explicitly their interaction. Contamination increased barnacle mortality and reduced predation with no effects on interaction strength. This was because the higher mortality of the prey compensated for the lower consumption of the predator. Despite not affecting the interaction strength, these results suggest a decrease in energy flow in the trophic chain that may lead to important changes in community structure and ecosystem functioning. This study shows the importance of manipulative experiments designed to provide mechanistic insights into ecological interactions to better clarify the effect of stressors on the structure and dynamic of communities. Graphical abstract: Unlabelled Image Highlights: Copper contamination increased mortality of a sessile prey. Copper decreased consumption of the prey by the predator. Predator-prey interaction strength was not affected by copper. Copper effects on predator-prey interactions may affect community dynamics.